Homoploid hybridization adds clarity to the origins of octoploid strawberries - Fan, Zhen; Liston, Aaron; Soltis, Douglas E.; Soltis, Pamela S.; Ashman, Tia-Lynn; Hummer, Kim E.; Whitaker, Vance M. (Proceedings of the National Academy of Sciences - PNAS, 2025)
The evolutionary histories of many polyploid plant species are difficult to resolve due to a complex interplay of hybridization, incomplete lineage sorting, and missing diploid progenitors. In the case of octoploid strawberry with four subgenomes designated ABCD, the identities of the diploid progenitors for subgenomes C and D have been subject to much debate. By integrating new sequencing data from North American diploids with reticulate phylogeny and admixture analyses, we uncovered introgression from an extinct or unsampled species in the clade of Fragaria viridis , Fragaria nipponica , and Fragaria nilgerrensis into the donor of subgenome A of octoploid Fragaria prior to its divergence from F. vesca subsp . bracteata . We also detected an introgression event from F. iinumae into an ancestor of F. nipponica and F. nilgerrensis. Using an LTR-age-distribution-based approach, we estimate that the octoploid and its intermediate hexaploid and tetraploid ancestors emerged approximately 0.8, 2, and 3 million years ago, respectively. These results provide an explanation for previous reports of F. viridis and F. nipponica as donors of the C and D subgenomes and suggest a greater role than previously thought for homoploid hybridization in the diploid progenitors of octoploid strawberry. The integrated set of approaches used here can help advance polyploid genome analysis in other species where hybridization and incomplete lineage sorting obscure evolutionary relationships.